THE EFFECT OF INTERVAL TRAINING ON THE MIDDLE DISTANCE RUNNING SPEED OF PASI BONE ATHLETES - Khalid Rijaluddin; Rahmat Ilahi; Rachmat Hidayat (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
The purpose of this study was to determine the effect of interval training on the speed of PASI Bone athletes. This study used quantitative research with an experimental design, the one group pretest-posttest design. The population of this study were all PASI Bone athletic athletes, for the sample of this study were male middle-distance runners as many as 12 samples from the total population. The research instrument was a test using a pretest and posttest. Data analysis used a normality test, a homogeneity test, and a hypothesis test using SPSS. Based on the results of the data test analysis, the normality test used the Shapiro Wilk method with the results of the 60-meter running speed pretest with a significant value of 0.077, then the p value was 0.077> 0.05, the posttest results with a significant value of 0.082, then the p value was 0.082> 0.05. The homogeneity test obtained the pretest and posttest values of the 60-meter run with ap value (sig.) 0.917> 0.05 and the results of the homogeneity test obtained the pretest value. Hypothesis testing using the t-test, from the results of the pretest and posttest of 60-meter running speed, the significance value of probability was 0.000 <0.05 and the t-count value> t-table (5.177> 0.000). Based on the results of the data analysis of the requirements test, it was found that the pretest and posttest speed data were normal and homogeneous. And based on the results of the t-test, there was an effect of interval training on the middle-distance running speed of PASI Bone athletes.